2020
DOI: 10.1177/1937586720910082
|View full text |Cite
|
Sign up to set email alerts
|

Using the Importance for Survival Scale to Identify Preferred Nature Scenes With Restorative Potential: A Qualitative Study

Abstract: Background: Evidence supports the use of images of nature scenes in healthcare settings to reduce stress and improve emotional well-being. However, the literature is diverse and provides no integrated system to identify nature scenes that provide most therapeutic benefit. Objective: The current study aimed to validate and extend results of a correlational study that found the Importance for Survival Scale (IFSS) useful for selecting generally preferred nature scenes with therapeutic potential. Methods: The cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In addition, we have identified opportunities to investigate whether the results of existing nature imagery research on eco-friendly products also apply to UI design more broadly (e.g., evendor websites of non-green products, or mobile health applications). To do so, IS researchers may also explore and validate the IFS scale [34] as a potential tool for selecting nature imagery for use in UI designs.…”
Section: General Discussion and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we have identified opportunities to investigate whether the results of existing nature imagery research on eco-friendly products also apply to UI design more broadly (e.g., evendor websites of non-green products, or mobile health applications). To do so, IS researchers may also explore and validate the IFS scale [34] as a potential tool for selecting nature imagery for use in UI designs.…”
Section: General Discussion and Future Researchmentioning
confidence: 99%
“…A recent study by Thake and colleagues [34] identified six environmental elements as being critical for triggering Biophilic responses (water, vegetation, vantage, weather, protection, and access). Adopting an environmental psychology approach in line with SRT, Thake and colleagues created the Importance For Survival (IFS) scale, containing 16 items to identify the restoration potential of a nature image.…”
Section: Nature Elementsmentioning
confidence: 99%
See 1 more Smart Citation